PENGARUH KEMAMPUAN GURU DALAM PENGELOLAAN KELAS TERHADAP MINAT BELAJAR PESERTA DIDIK KELAS IV SD NEGERI 3 KETEGUHAN - Amara, Dela; Nureva, Nureva; Soraya, Rahayu (STKIP Al Islam Tunas Bangsa, 2024)
This research aims to determine the significant influence of teachers' abilities in classroom management and students' low interest in learning. The type of research used is quantitative research. The population was 54 students and the research sample was 34 students. Data collection techniques are observation, interviews, questionnaires and documentation studies. The data collection instrument was a questionnaire with a Likert scale, which was previously tested for validity and reliability. The results of the research show that there is an influence of teacher ability on interest in learning, and classroom management on the interest in learning of class IV students at SDN 3 Keteguhan. This can be seen from the influence of the multiple linear regression test and hypothesis testing (F test) using the formula. If Fcount ≥ Ftable, then Ho is rejected, meaning it is significant, namely Fcount 18.870 ≥ Ftable 3.276. This means that there is a significant influence on the influence of teacher ability and classroom management on the learning interest of class IV students at SDN 3 Keteguhan.